Semisweet chocolate as a vehicle for the probiotics Lactobacillus acidophilus LA3 and Bifidobacterium animalis subsp. lactis BLC1: Evaluation of chocolate stability and probiotic survival under in vitro simulated gastrointestinal conditions. (January 2017) - Silva, Marluci P.; Tulini, Fabricio L.; Marinho, Júlia F.U.; Mazzocato, Marcella C.; De Martinis, Elaine C.P.; Luccas, Valdecir; Favaro-Trindade, Carmen S.
Abstract: Semisweet chocolate pleases a broad range of consumers, but it is an underexplored food matrix among probiotic products. Thus, this study aimed to evaluate semisweet chocolate as a vehicle for probiotics ( Lactobacillus acidophilus LA3 and Bifidobacterium animalis subsp. lactis BLC1). The chocolates were evaluated by aw, pH, surface color and morphology, hardness, microbiological quality, sensorial acceptance and probiotic viability. Besides, probiotic survival in simulated gastric and intestinal fluids (SGF/SIF) was evaluated before and after application in chocolate. Samples presented pH values around 6 and aw below 0.6. Free probiotics populations were reduced after exposure to SGF/SIF, while no significant reduction was detected in probiotic populations incorporated into chocolate. After 120 days of storage at 25 °C, probiotic populations in chocolate were reduced by only 1.4 and 0.7 logarithmic cycles, respectively. Considering these results and that all samples were very well accepted by panelists, semisweet chocolate can be considered a good vehicle for probiotics. Highlights: LA3 and BLC1 did not affect physical and chemical characteristics of semisweet chocolate. Probiotic populations in chocolate kept unchanged during 120 days of storage at 25 °C. Chocolate improved probiotic survival in simulated gastrointestinal fluids. Probiotic semisweet chocolates were very well accepted by 100 panelists.